ANALYSIS OF SALIVARY PROTEINS AS THE BIOCHEMICAL INDICATORS OF NUTRITIONAL STATUS AND SALIVARY GLAND FUNCTION - MAHADEVAN K; VELAVAN S (International Journal of Pharma and Bio Sciences, 2013)
Saliva is increasingly used and well validated in diagnosing, monitoring health and disease status, mainly due to its origin, composition, functions, and interactions with other organ systems.The effect of nutrition status on saliva covers a broad spectrum of factors. This includes the degree of malnutrition, the period when malnutrition takes place, the consistency of the diet, the effect on salivary gland growth and function, and the effects on the different salivary glands. Protein-energy malnutrition (PEM) is a serious nutritional problem in slum children’s and elder. Serum albumin, globulin, transferring, total protein and amylase activity have been used as biochemical indicators of protein nutritional status and salivary gland functions, but taking blood from the slum subjects are difficult and invasive. We therefore assessed the possibility of using saliva as noninvasive materials to estimate concentrations of albumin, transferrin, total protein and amylase activity. Saliva is collected from 155 slum and healthy subjects of different ages and control (aged 8-15, 24- 32, 58-77 yrs) and the concentrations of albumin, transferrin, total protein and amylase activity in saliva were evaluated. Altered levels of protein profile were observed in this study. This result suggested that nutritional deficiencies compromise salivary gland function, thus increasing susceptibility to dental caries and oral infections and reducing quality of life.